PENGARUH PERSEPSI HARGA, LOKASI, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PROPERTY DI ANDARI PROPERTY BADUNG - I Gede Bagus Wiguna Dananjaya; Ni Putu Nina Eka Lestari; I Wayan Sunia (Berajah Journal, 2026)
This research is expected to help evaluate and serve as a basis for consideration in determining marketing strategies that can meet consumer tastes and desires when purchasing property. This research was conducted at Andari Property Badung, located at Jalan Muding Indah No. 121, Kerobokan Kaja, Badung Regency. The research focused on marketing related to price, location, promotion, and consumer/customer purchasing decisions. The reason for this research is that based on the Andari Property Badung database, the population and sample consisted of 41 respondents. Quantitative and qualitative data sources include primary and secondary data collected through documentation, questionnaires, and online data searches. The data analysis methods used were Classical Assumption Testing and Multiple Linear Regression Analysis using SPSS 26.0. Based on the results of the discussion above, it can be concluded that this study is: Partially Has a Positive and Significant Influence Between Price Variables (X₁) on Purchasing Decisions (Y), Partially Obtained a T-Count Value of 2.249 with a Significance Level Value of 0.31. Partially Has a Positive and Significant Influence Between Place/Location Variables (X₂) on Purchasing Decisions (Y), Partially Obtained a T-Count of 5.037 with a Significance Level Value of 0.000. Partially Has a Passive and Significant Influence Between Promotion Variables (X₃) on Purchasing Decisions (Y), Partially Obtained a T-Count of 3.231 with a Significance Level of 0.003. Simultaneously, there is a positive and significant influence between the influence of price (X₁), place/location (X₂), and promotion (X₃) on purchasing decisions (Y). Simultaneously, the influence of price (X₁), place/location (X₂), and promotion (X₃) on purchasing decisions (Y) obtained an F count of 17.180 with a significance value of 0.000.